2008
DOI: 10.1016/j.jpsychires.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Reduced hedonic capacity in major depressive disorder: Evidence from a probabilistic reward task

Abstract: Objective-Anhedonia, the lack of reactivity to pleasurable stimuli, is a cardinal feature of depression that has received renewed interest as a potential endophenotype of this debilitating disease. The goal of the present study was to test the hypothesis that individuals with major depression are characterized by blunted reward responsiveness, particularly when anhedonic symptoms are prominent.Methods-A probabilistic reward task rooted within signal-detection theory was utilized to objectively assess hedonic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

52
720
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 664 publications
(785 citation statements)
references
References 64 publications
52
720
13
Order By: Relevance
“…As Pizzagalli and colleagues (2008) found that the response bias development completed between first and third block was uninformative in their experiment, they further computed reward learning expressed within the first round only. This parameter was derived in the same manner as above, but comparing response bias in the first half of first block with response bias in the latter half of the same block.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…As Pizzagalli and colleagues (2008) found that the response bias development completed between first and third block was uninformative in their experiment, they further computed reward learning expressed within the first round only. This parameter was derived in the same manner as above, but comparing response bias in the first half of first block with response bias in the latter half of the same block.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental procedure replicated the probabilistic reward signal-detection task previously designed by Tripp and Alsop (1999) and adapted by Pizzagalli et al (2005, 2008) and Santesso et al (2008) (see Figure 1). In brief, this task presents 300 trials in three blocks.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations